Inductive Logic Programming 24th International Conference, ILP 2014, Nancy, France, September 14-16, 2014, Revised Selected Papers - Davis, Jesse; Ramon, Jan (Lecture Notes in Artificial Intelligence, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the 24th International Conference on Inductive Logic Programming, ILP 2014, held in Nancy, France, in September 2014. The 14 revised papers presented were carefully reviewed and selected from 41 submissions. The papers focus on topics such as the inducing of logic programs, learning from data represented with logic, multi-relational machine learning, learning from graphs, and applications of these techniques to important problems in fields like bioinformatics, medicine, and text mining.